The 28 November 2020 Landslide, Tsunami, and Outburst Flood – A Hazard Cascade Associated With Rapid Deglaciation at Elliot Creek, British Columbia, Canada. Issue 6 (29th March 2022) - Geertsema, M.; Menounos, B.; Bullard, G.; Carrivick, J. L.; Clague, J. J.; Dai, C.; Donati, D.; Ekstrom, G.; Jackson, J. M.; Lynett, P.; Pichierri, M.; Pon, A.; et al.
Abstract: We describe and model the evolution of a recent landslide, tsunami, outburst flood, and sediment plume in the southern Coast Mountains, British Columbia, Canada. On November 28, 2020, about 18 million m 3 of rock descended 1, 000 m from a steep valley wall and traveled across the toe of a glacier before entering a 0.6 km 2 glacier lake and producing >100‐m high run‐up. Water overtopped the lake outlet and scoured a 10‐km long channel before depositing debris on a 2‐km 2 fan below the lake outlet. Floodwater, organic debris, and fine sediment entered a fjord where it produced a 60+km long sediment plume and altered turbidity, water temperature, and water chemistry for weeks. The outburst flood destroyed forest and salmon spawning habitat. Physically based models of the landslide, tsunami, and flood provide real‐time simulations of the event and can improve understanding of similar hazard cascades and the risk they pose. Plain Language Summary: Glacier retreat exposes unstable slopes that can suddenly fail. We describe and model one such event with far‐reaching consequences. The landslide mass (50 million tonnes, equivalent to the combined mass of all Canadian automobiles) entered and suddenly drained a 0.6‐km 2 alpine lake in the southern Coast Mountains of British Columbia. Displaced water destroyed salmon‐spawning habitat over a distance of 8.5 km and created a plume of sediment and organic matter more than 60 km from the head of the fjord into which the floodwaters discharged. Physically based models are able to simulate the hazard cascade, and such models could be used to improve hazard and risk assessments of these events under future climate change. Key Points: Rapid glacier retreat created conditions that allowed a geohazard cascade to occur in a steep mountain valley We describe and model a recent landslide, tsunami, and outburst flood that typifies a deglacial geohazard cascade Future work should predict new glacial lakes and use physically based models to simulate the slope, tsunami, and outburst flood hazards